The Value of the Internet for Consumers - Smaranda Pantea; Bertin Martens (European Commission, Joint Research Centre (JRC), 2014)
Several studies have examined the market value of paid-for internet services and internet access. This paper estimates the value of leisure time spent online for which the consumer pays no monetary price and which has become increasingly important as a leisure activity. We apply a methodology developed be Goolsbee and Klenow (2006), which relies on differences in time spent online and opportunity cost of time, to an internet users' clickstream dataset for the five largest economies in the European Union (Germany, United Kingdom, France, Italy and Spain). We find that, according to our most conservative measure, leisure time spent on the internet generated a consumer surplus of between 0.6 and 1% of full income in 2011 in the countries studied. The total consumer surplus for each country amounted to between 18 billion euros (Italy) and 44 billion euros (Germany).
Keywords: D12; D6; L86; 330; Internet Services; Consumer Surplus; Leisure